2016
DOI: 10.1016/j.electacta.2016.05.188
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Oxygen content on the electrochemical behavior of Ta1-xOx coatings

Abstract: In this study, Ta 1-x O x coatings were deposited by reactive magnetron sputtering aiming at the enhancement of the electrochemical stability stainless steel 316L. The coatings were produced using variable oxygen content in order to determine its influence on the films morphological features and corrosion resistance. Structural and morphological characteristics were correlated with the corrosion behavior in artificial saliva. Potentiodynamic and electrochemical impedance spectroscopy tests were complemented wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 34 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…The Bode curves for the ZrN, ZrN+1Ag, and ZrN+2Ag coatings show the formation of two-time constants related to the defects in the coating, providing a direct diffusion path for the corrosive media [3] and to the double-layer capacitance [3,43]. Some authors have reported that the presence of two-time constants is typical for porous coatings [3,[43][44][45]. Finally, at 1 h, the impedance module diagram (Figure 7a) showed better performance of all the samples compared to the 316L stainless steel.…”
Section: Corrosion Resistance Of the Coatingsmentioning
confidence: 95%
“…The Bode curves for the ZrN, ZrN+1Ag, and ZrN+2Ag coatings show the formation of two-time constants related to the defects in the coating, providing a direct diffusion path for the corrosive media [3] and to the double-layer capacitance [3,43]. Some authors have reported that the presence of two-time constants is typical for porous coatings [3,[43][44][45]. Finally, at 1 h, the impedance module diagram (Figure 7a) showed better performance of all the samples compared to the 316L stainless steel.…”
Section: Corrosion Resistance Of the Coatingsmentioning
confidence: 95%
“…Magnetron sputtering method [318][319][320] High speed of coating formation at low vacuum of 0.1-1 Pa; no overheating of the substrate. Magnetron sputtering can be carried out both on direct and alternating currents.…”
Section: Physical Techniquesmentioning
confidence: 99%
“…Tantalum oxide (Ta 2 O 5 ) micro-structured coatings present interesting properties that make them suitable for a large range of applications. These coatings are used for storage capacitors and resistors in electronic [ 1 , 2 ] and microelectronic industries [ 1 , 3 , 4 ] because they show a high dielectric strength, high melting point and thermal stability [ 5 ], excellent corrosion [ 6 , 7 , 8 , 9 ], and abrasion resistance [ 10 ], which make them also a reliable option for biomedical instruments [ 6 , 7 , 11 , 12 , 13 , 14 ] and chemical equipment (e.g., optical devices) [ 15 ]. They are biocompatible [ 16 , 17 , 18 , 19 ] too, being a good option for bioengineering implants application [ 6 , 11 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%